Administrative theory and military force: An analysis of the main contributions of classical administrative theories to management in the military forces - Ortiz-Bethés, Carlos Ernesto (EFIM Ediciones, 2018)
The practice of the administration of the first half of the 20th century along with its theorization has been framed in the light of three administrative paradigms: The techno-engineering para-digm, the sociological paradigm and the humanistic psychological paradigm that have given bir-th to classical theories of the Administration, such as the Scientific Administration of Taylor, the Classical Administration of Fayol, The Theory of Human Relations of May and The Bureaucracy of Weber, all with a distinctive conceptual framework that have aimed at solving the organizational problems of companies in their respective historical contexts and that still continue to be very useful, not only to private companies, but also to state organizations. Hence the analysis of this document that presents the main contributions of the classical theories of the administration of the first half of the twentieth century to the management of military forces around three topics: Tasks, social interactions and relations between power in hierarchical structures.